Cultura y Salud: es hora de actuar European Commission: Directorate-General for Education, Youth, Sport and Culture. (2025). Culture and health : time to act : executive summary. Publications Office of the European Union - Ávila-Valdés, Noemí (Arte, Individuo y Sociedad, 2026)